Internationally trained nurses and host nurses’ perceptions of safety culture, work-life-balance, burnout, and job demand during workplace integration: a cross-sectional study - Roth, Catharina; Berger, Sarah; Krug, Katja; Mahler, Cornelia; Wensing, Michel (BMC nursing, 2021)
The shortage of qualified nurses is a problem of growing concern in many countries. Recruitment of internationally trained nurses has been used to address this shortage, but successful integration in the workplace is complex and resource intensive. For effective recruitment and retention, it is important to identify why nurses migrate and if their expectations are met to ensure their successful integration and promote a satisfying work climate for the entire nursing team. The aim of this study was to examine the perceptions of safety culture, work-life-balance, burnout and job demand of internationally trained nurses and associated host nurses in German hospitals.
Gesehen am 02.03.2022